Childhood Abuse and Adolescent School Bullying: The Mediating Roles of Perceived Social Support and Loneliness. - Wang, Xiaorou; Xie, Ruibo; Ding, Wan; Song, Shengcheng; Wu, Wei; Wang, Xiaoyue; Li, Weijian (Journal of Child & Family Studies, 2023)
Childhood maltreatment has been evidenced to be a risk factor for adolescent victimization or bullying. However, the impact of different types of childhood maltreatment (emotional and physical abuse) on adolescent victimization/bullying and its underlying mechanisms are not yet well clarified. Therefore, based on the framework of "Family-Individual-School", we explored the mediating roles of perceived social support and loneliness in the effect of childhood emotional/physical abuse on adolescent victimization/bullying. Meanwhile, we also examined the gender differences that exist in the mechanisms. A total of 3600 Chinese adolescents (M (SD) = 16.21 (0.99), 63.36% males) completed questionnaires. The findings found that perceived social support and loneliness played a chain mediating role in the relationship between childhood maltreatment and adolescent victimization/bullying. The abuse discrepancy results suggest that only emotional abuse couldn't predict adolescents' bullying. Childhood physical abuse has a greater impact on bullying than on victimization. Compared with physical abuse, emotional abuse is more likely to influence adolescents' victimization/bullying through loneliness. Gender difference results showed that male adolescents' perceived social support is a better predictor of their bullying behavior than females. Females' physical abuse couldn't predict loneliness and females' perceived social support couldn't predict their victimization. Enhancing the perceived social support and reducing loneliness should be emphasized in interventions to reduce the school bullying of Chinese adolescents who have suffered childhood maltreatment. The results also provide insights into the intervening measures for school bullying based on gender differences. Highlights: Childhood maltreatment can further influence adolescent victimization/bullying through individual factors. Emotional and physical abuse have different effects on adolescent victimization and bullying. There are gender differences in the influence of childhood maltreatment on adolescent victimization/bullying.